Block Matrix Preconditioner for the Coupled Volume-Surface Integral Equation - Tao, Shifei (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A Block Matrix Preconditioner (BMP) for Volume and Surface Electric Field Integral Equations (V-EFIE and S-EFIE) for the analysis of electromagnetic scattering problems is presented. The V-EFIE operator is well-posed while the S-EFIE operator is ill-posed, so for the coupled V-EFIE and S-EFIE system, it is illconditioned. Therefore, the solution time is very long if the iterative solution is applied to solve the system equations. The proposed scheme constructs a sparse matrix version of each block matrix, which is followed by the inversion of the resultant block sparse matrix using incomplete factorization. The proposed scheme enables the efficient electromagnetic analysis for the composite structures. Several numerical examples are proposed to demonstrate the efficiency of the scheme.